Pengembangan E-Modul Kimia Berbantuan Flip Pdf Professional Untuk Pembelajaran Kimia Non Logam Pada Pokok Bahasan Karbon Dan Silikon - Lusyana Rahman; Ramlan Silaban; Nurfajriani Nur (Neolectura, 2021)
A good learning process can be realized if it is supported by quality learning resources and learning media. So that one of the efforts that educators can do is to innovate in the development of learning resources and learning media. This study aims to produce a chemistry e-module assisted by Flip Pdf Professional as a learning media and learning resource that is suitable for use in learning non-metal chemistry on the subject of carbon and silicon. This research is a development research (R&D) with the ADDIE model. The data collection instrument used was a validation questionnaire based on the National Education Standards Agency (BSNP). Data were analyzed by qualitative descriptive and descriptive statistical analysis. The results showed the feasibility of the chemistry e-module developed with an average score of 3.61 or 90.4% and included in the